Stabilization and Control of Fractional Order Systems: A Sliding Mode Approach - Bijnan, Bandyopadhyay (Springer, 2015)
In the last two decades fractional differential equations have been used more frequently in physics, signal processing, fluid mechanics, viscoelasticity, mathematical biology, electro chemistry and many others. It opens a new and more realistic way to capture memory dependent phenomena and irregularities inside the systems by using more sophisticated mathematical analysis.